1971
DOI: 10.1159/000121977
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Systemic and Intracerebral Administration of Two Opposite Acting ACTH-Related Peptides on Extinction of Conditioned Avoidance Behavior

Abstract: The effects of the decapeptide ACTH-(1–10) and [D-phe7]-ACTH-(1–10) were tested on the rate of extinction of a pole-jumping avoidance response in rats. ACTH-(1–10) in doses of 20, 50, and 100 µg inhibited extinction of the avoidance response 4 h following subcutaneous administration. [D-phe7]-ACTH-(1–10) in doses of 20, 50, and 100 µg facilitated extinction 4 h after injection. Intracerebral implantation of approximately 10 µg of these ACTH-analogues in the freely moving rat had similar e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(13 citation statements)
references
References 4 publications
(5 reference statements)
2
11
0
Order By: Relevance
“…However, intracerebroventricular (i.c.v.) and local microinjection of ACTH and vasopressin produce an impairment of extinction retention similar to that obtained with systemic injections but without the concomitant changes in autonomic responses indicative of a stress reaction, 240,241,249,250 and ACTH attenuates extinction just as effectively in appetitive paradigms as in aversive ones. 251 Finally, ACTH might strengthen CS-US associations formed during acquisition.…”
Section: Neurotransmitter Systemsmentioning
confidence: 66%
“…However, intracerebroventricular (i.c.v.) and local microinjection of ACTH and vasopressin produce an impairment of extinction retention similar to that obtained with systemic injections but without the concomitant changes in autonomic responses indicative of a stress reaction, 240,241,249,250 and ACTH attenuates extinction just as effectively in appetitive paradigms as in aversive ones. 251 Finally, ACTH might strengthen CS-US associations formed during acquisition.…”
Section: Neurotransmitter Systemsmentioning
confidence: 66%
“…Active avoidance behavior was studied in a pole jumping avoidance situation (Van Wimersma Greidanus and De Wied, 1971). Animals were trained to jump onto a pole placed vertically in the box, in order to escape or avoid a scrambled electric foot shock (EFS, 0.25 mA) which could be presented through the grid floor of the box.…”
Section: Methodsmentioning
confidence: 99%
“…Searching for the CNS sites of action of these neuropeptides in relation to avoidance behavior several brain areas appear to be involved in their inhibitory effects on extinction of an active avoidance response. Implantation studies point to the posterior thalamic area including the parafascicular nuclei as a site of action of ACTH [43] as well as vasopressin [47]. Lesion studies however indicated that this parafascicular area is less essential for vasopressin in relation to its inhibitory effect on avoidance extinction than for ACTH4_., [48].…”
mentioning
confidence: 99%
“…Implantation studies point to the posterior thalamic area including the parafascicular nuclei as a site of action of ACTH [43] as well as vasopressin [47]. Lesion studies however indicated that this parafascicular area is less essential for vasopressin in relation to its inhibitory effect on avoidance extinction than for ACTH4_., [48].…”
mentioning
confidence: 99%